2009
DOI: 10.1080/00032710802421897
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free DNA Biosensor for Electrochemical Detection of Short DNA Sequences Related to Human Papilloma Virus

Abstract: Highly sensitive label-free techniques of DNA determination are particularly interesting in relation to the present development of an electrochemical hybridization biosensor for the detection of short DNA fragments specific to the human papilloma virus (HPV). Unlabeled DNA probes have been immobilized by spontaneous coadsorption of thiolated single-stranded oligonucleotides (HS-ssDNA) onto the sensing surface of a screen-printed gold electrode (SPGE). The covalently immobilized single-stranded DNA probe (HS-ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…93%-100% of worldwide invasive carcinomas have been shown to be associated with a limited spectrum of HPV types, mostly HPV 16 and 18 (Zari et al, 2009). The detection of DNA sequences is of central importance to the virus and genetic detection, and early diagnosis of diseases (Wang et al, 2011a;Lu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…93%-100% of worldwide invasive carcinomas have been shown to be associated with a limited spectrum of HPV types, mostly HPV 16 and 18 (Zari et al, 2009). The detection of DNA sequences is of central importance to the virus and genetic detection, and early diagnosis of diseases (Wang et al, 2011a;Lu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For times of 15, 30, 60 and 120 minutes, there was coverage of about 38 %, 19 %, 29 % and 40 %, respectively (data not shown). Evaluation of the stability of the SAM by successive scans (ten cycles) in K 4 Fe(CN) 6 solution showed that the SAM formed after 120 minutes was the most stable, with minimal loss of coating. For the other formation times there was a decrease of the SAM at the third cycle.…”
Section: Evaluation Of the Sam On The Cdtrodesmentioning
confidence: 99%
“…The analysis of the percentage of SAM on the CDtrode surfaces was performed by calculating the oxidation peak area of K 4 Fe(CN) 6 , before and after modification with lipoic acid. For times of 15, 30, 60 and 120 minutes, there was coverage of about 38 %, 19 %, 29 % and 40 %, respectively (data not shown).…”
Section: Evaluation Of the Sam On The Cdtrodesmentioning
confidence: 99%
“…After hybridization, DNA is treated with an acid, and the acid-released purine bases are directly determined by SWV with HPV sequence detection limit of 2 pg·mL −1 (S/N =3). 100 The specific sequence for hepatitis C virus-1 (HCV-1) was detected by Pournaghi-Azar et al, 101 using a label-free DNA hybridization biosensor. The sensor relied on the immobilization of a 20-mer oligonucleotide (containing 2 guanines and 11 cytosines) as a probe on the pencil graphite electrode.…”
Section: Nucleic Acid Electrochemical Biosensorsmentioning
confidence: 99%